2007
DOI: 10.5254/1.3539414
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Latex-State 13C-NMR Spectroscopy for Natural Rubber Vulcanizates

Abstract: Crosslinking junctions of natural rubber vulcanizates were characterized by high-resolution latex-state 13C-NMR spectroscopy. Vulcanized natural rubber latex was prepared by two methods: i.e., vulcanization of the rubber latex and cryogenic crushing of a rubber sheet vulcanized on a hot press. High-resolution latex-state 13C-NMR spectroscopy was attained even after vulcanization of the rubber latex, as is evident from no background in spectrum and narrow half width of signals independent of vulcanization time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
3
9
1
Order By: Relevance
“…Figure 6 shows plausible cross-linking junctions of cross-linked natural rubber. The present and previous works 7,[20][21] demonstrate that the tertiary and quaternary carbons linked to sulfur may be neighbors to carbon-carbon double bonds in trans form. As shown in Figure 6, the quaternary carbon linked to sulfur at a cross-linking junction may maintain the accordion structure of natural rubber, which is a main factor in the rubber elasticity.…”
Section: Resultssupporting
confidence: 65%
“…Figure 6 shows plausible cross-linking junctions of cross-linked natural rubber. The present and previous works 7,[20][21] demonstrate that the tertiary and quaternary carbons linked to sulfur may be neighbors to carbon-carbon double bonds in trans form. As shown in Figure 6, the quaternary carbon linked to sulfur at a cross-linking junction may maintain the accordion structure of natural rubber, which is a main factor in the rubber elasticity.…”
Section: Resultssupporting
confidence: 65%
“…The active molecular motion of the rubbers at 50°C was found to be important for the quantitative analysis of the epoxy group content for EDPNR‐1, EDPNR‐2, EDPNR‐3, and EDPNR‐4, whose glass transition temperatures ( T g ) were about −58.6°C, −51.5°C, −46.7°C, and −43.3°C, respectively. This is consistent with the previous result that the high resolution is achieved at T ‐ T g >70 K for the latex‐state NMR spectroscopy …”
Section: Resultssupporting
confidence: 93%
“…Many trans-type species were generated in the sample prepared under general NR vulcanization conditions. The methine carbon signals of vulcanized junction points at 53.0–54.4 and 49.0–50.1 ppm in Figure d and in the DEPT135 spectrum (Figure e) were attributed to the reported crosslinked structures A and D, ,,,− although our assignments for both A and D were inconsistent with those of the previous NMR studies (see Table S5). Detailed assignments in the 48–60 ppm region are displayed in Figure .…”
Section: Resultscontrasting
confidence: 82%
“…These studies reported the presence of carbon signals of possible crosslinking points in structures A−C, H, and I 47 (Figure 2a) and predicted the crosslinked structures D−F. 42,43 However, many questions remain. First, unlike commercial NR products, the samples used in the above studies were prepared without the kneading or heat pressing stages commonly used for preparing NR products (see Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%